God's foreknowledge & man's free will - Rice, Richard (Bethany House, 1985)
This book gives new perspectives on one of the most fundamental issues of the christian faith: The relationship of God to his creation and the reality and extent of human freedom. - Introduction, 1. The conventional view of God, 2. The open view of God, 3. Creation and the openness of God, 4. Evil and the openness of God, 5. The future and the openness of God, 6. Providence and the openness of God, 7. Prophecy and the openness of God, 8. Predestination and the openness of God, 9. Personal religion and the openness of God